A Systematic Methodology for Optimal Design of Wireless Power Transfer System Using Genetic Algorithm - Anahita Bagheri; Abbas Erfanian; Adib Abrishamifar (Energies, 2020)
This paper presents a systematic methodology for the optimal design of wireless power transfer (WPT) systems. To design a WPT for a specific application, the values of coil geometric parameters and the number of resonators should be chosen such that an objective function is maximized while satisfying all the design constraints. The conventional methodologies, which are based on cyclic coordinate optimization, are not comprehensive and efficient methods. This paper presents a design methodology based on the genetic algorithm (GA). The optimization method has been applied to designing different WPTs with series and parallel connections of load and different design constraints. Moreover, the number of resonators is considered as the design parameters. In addition, WPTs with parallel and series connections of load are compared from different aspects. The results of calculation, simulation and measurements demonstrate that the 2-coil WPT can be optimized to achieve maximum efficiency compared to the previously reported 2-coil and multi-coil WPTs. In a fabricated 2-coil configuration, a power transfer efficiency (PTE) of 82.7% and a power delivered to the load (PDL) of 173.89 mW are achieved.